Financial Feasibility Analysis Of Urban Waste Processing As Refused Derived Fuel For Cement Company - Suherman Yahya; Betty Susanti; Heni Fitriani (Eduvest - Journal of Universal Studies, 2024)
Waste generated from community life activities continues to increase along with economic development and population growth. Systematic, comprehensive, and sustainable waste management is needed to overcome problems related to waste generation, both through efforts to reduce and handle waste. One waste management innovation is using fuel waste, called Refuse Derived Fuel (RDF). Utilization of RDF can process waste on a large scale and can be a substitute for fossil fuels for industry, one of which is the cement industry. This research analyzes the financial feasibility of processing waste into RDF for cement factories. The case study was carried out at a landfill in Ogan Komering Ulu Regency - South Sumatera Province, with PT. Semen Baturaja Tbk as offtaker of RDF. Financial feasibility analysis uses Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI) indicators. A sensitivity analysis of financial feasibility was carried out on changes in RDF selling prices and operational costs. This analysis of the scenario 1 (70 % equity : 30 % debt) and the scenario 2 (30 % equity : 70 % debt) shows that the Project of RDF Plant is feasible to implement. Sensitivity analysis of scenario 1 and 2 are not feasible at 20% decrease in selling price and scenario 2 is not feasible at 20% increase in investment.